(untitled) (American Journal of Islam and Society, 2002)
Language, perhaps the most mysterious element of human existence, enables us to acquire some insight into the human spirit. When used as an instrument for expressing ideas and sharing feelings, it helps externalize individual consciousness and makes it accessible to others. But it is also an instrument for shaping individual consciousness by means of internalizing notions and ideas shaped by others. Human consciousness, both individual and collective, thus presupposes language. Language and discourse are essential for any collective action. While such individual actions as hunting for food or constructing a dwelling may arguably be possible without these abilities, collective action requires the development of shared meaning and common understanding through linguistic discourse. The greater the collectivity and the more profound and far-reaching the collective enterprise is, the more universal and abstract the language becomes. Thus religion and philosophy have always been central to human civilization. Yet despite the proximity between words and concepts, or language and discourse, the two are far from identical. Although words denote concepts and a discourse consists oflinguistic terms, the meaning embedded in words and terms is ultimately determined by social experiences and psychological states. Hence, in different social milieu and sociohistorical contexts, what some consider as "courage" might be regarded by others as "insanity," and what one generation might regard as "prudence" may denote "cowardice" in another. Evidently, meaning lies not in individual words but in conceptual frameworks and historically situated discourses. Take, for instance, such concepts as freedom, equality, dignity, or tolerance. These concepts often struck a cord among people of different cu 1- tures and ideological persuasions. But whether these words have a positive impact on people hinges not merely on their abstract meaning, but on how ...